DETERMINANTS OF INVESTMENT INTEREST OF THE JAMBI CITY COMMUNITY IN THE CAPITAL MARKET - Rafika Gina Setiawan; Afrizal; Rita Friyani (Transpublika Publisher, 2023)
The main goal of the study is to investigate how factors like investment knowledge, investment returns, investment risk, and the bandwagon effect affect people's propensity to make investments in Jambi City. The study focuses on residents of Jambi City who have a Single Investor Identification (SID). Using the Slovin formula and a straightforward random sampling strategy, samples were chosen. Respondents were given questionnaires utilizing descriptive approaches throughout the first round of data collection. The outcomes indicate that the community's inclination to engage in capital market investments is significantly shaped by their investment knowledge, investment returns, and the influence of the bandwagon effect. Conversely, the impact of investment risk on the community's willingness to participate in capital market investments appears to be less substantial. It's worth noting that the coefficient of determination (R Square) illustrates that the independent variables effectively explain investment interest, with approximately 36% of this interest attributed to factors not encompassed within the model.